Download composite file - Reviews, All (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Ballard, Michel (2001). Le nom propre en traduction. John D. Gallagher Bradford, Lisa Rose (compiladora) (2001). La cultura de los géneros. Ilse Logie Calvin, William H. & Derek Bickerton (2000). Lingua ex machina: reconciling Darwin and Chomsky with the Human Brain. Eva Nunez-Mendez Krüger, Mechtild (2001).Übersetzungskompetenz: modale Semantik. Eine Studie am Sprachenpaar Dänisch-Deutsch. Leona Van Vaerenbergh Le Goffic, Pierre (éd.) (2001). Le présent en français. Fabienne Martin